2013
DOI: 10.3389/fnhum.2013.00757
|View full text |Cite
|
Sign up to set email alerts
|

Grapheme learning and grapheme-color synesthesia: toward a comprehensive model of grapheme-color association

Abstract: Recent progress in grapheme-color synesthesia research has revealed that certain regularities, as well as individual differences, figure into grapheme-color associations. Although several factors are known to regulate grapheme-color associations, the impact of factors, including their interrelationships, on synesthesia remains unclear. We investigated determinants of synesthetic color for graphemes (characters, letters) of Hiragana, a phonetic script in the Japanese language, and the English alphabet. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 18 publications
5
50
0
Order By: Relevance
“…Eagleman (2010) argued that letters early in their respective alphabets (e.g., A, B, C, D) tended to be associated with colors that are more distinct from each other, whereas letters that come later (e.g., V, W, X, Y) tended to be associated with colors that were quite similar to each other. This ordinal relationship has also been found for Japanese hiragana characters (Asano & Yokosawa, 2013).…”
mentioning
confidence: 61%
“…Eagleman (2010) argued that letters early in their respective alphabets (e.g., A, B, C, D) tended to be associated with colors that are more distinct from each other, whereas letters that come later (e.g., V, W, X, Y) tended to be associated with colors that were quite similar to each other. This ordinal relationship has also been found for Japanese hiragana characters (Asano & Yokosawa, 2013).…”
mentioning
confidence: 61%
“…Price and Pearson (2013) similarly suggest that sequence-space synaesthesia may arise due to active visual imagery which aids in learning sequenced stimuli. These kinds of hypotheses have been presented as an alternative to models based on cross-activation or disinhibition between cortical areas (Mroczko-Wasowicz and Nikoliü, 2014) or as "challenging a view that synesthesia requires unusual hard-wired crossassociations between certain brain areas" (Asano and Yokosawa, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a hangul consonant 'ㄱ' can be associated with different phonemes, though the initial phoneme remains the same. These two characteristics shared by hangul were suggested as what might be behind the discrepancy of previous studies on the determinants of synesthetic color using Latin alphabet and Japanese scripts (Asano and Yokosawa, 2013). Therefore, hangul was expected to provide a clue to estimate the importance of sound as a determinant of synesthetic color.…”
Section: Introductionmentioning
confidence: 96%
“…The choice of Japanese scripts in the latter studies was, as the authors themselves emphasized, based on the shallow orthography (i.e., simple and consistent correspondence between character and sound) of the Japanese language, in contrast to the deep orthography (i.e., complex and inconsistent correspondence between character and sound) found in English. In a more recent work, they also suggested that a Latin alphabet grapheme is different from a Japanese character by having two kinds of phonological information -i.e., its name and its pronunciation, which might weaken the influence of sound on synesthetic colors induced by Latin alphabet grapheme (Asano and Yokosawa, 2013). Asano and Yokosawa suggested that those studies showing the important role of shape over sound in determining synesthetic color might be due to the choice of the particular stimuli (Latin alphabet) and its intrinsic characteristics.…”
Section: Introductionmentioning
confidence: 98%